Communicating uncertainty in monetary policy - Sharon Kozicki; Jill Vardy (Bank of Canada, 2017)
While central banks cannot provide complete foresight with respect to their future policy actions, it is in the interests of both central banks and market participants that central banks be transparent about their reaction functions and how they may evolve in response to economic developments, shocks, and risks to their outlooks. This paper outlines the various ways in which the Bank of Canada seeks to explain its economic outlook and monetary policy decisions, with an emphasis on how different sources of uncertainty factor into monetary policy communications. To help markets and others understand its reaction function, the central bank must explain what uncertainties are weighing on policy and how (or if) these uncertainties are being considered in policy formulation. Discussion of uncertainty becomes particularly important when a large shock has hit the economy or when a central bank's view or its policy stance is changing. Market views and the views of the central bank will not always be aligned. The aim of monetary policy communications should not be alignment but understanding - helping markets comprehend the central bank's policy objectives and providing a coherent rationale for policy decisions. In doing so, the bank must be transparent about the uncertainties influencing the outlook, their possible impacts and how these uncertainties will be factored into policy decisions. This paper outlines some recent and upcoming initiatives to achieve those objectives and improve Bank of Canada communications.
Keywords: E; E5; E52; E58; E61; 330; Credibility; Monetary Policy; Monetary Policy Implementation; Uncertainty and Monetary Policy